Operations management - Stevenson, William J. (Boston : McGraw-Hill/Irwin, 2007)
"The Eighth Edition of Operations Management offers the most complete, balanced, and flexible operations management coverage. The most widely used text in the field, this new edition offers everything you would expect from a leading and innovative learning tool. Combining balanced coverage of quantitative and qualitative operations management topics, Stevensons' tradition of clearly written explanations, and comprehensive innovative technology integration, the Eighth Edition introduces a new contemporary design, and updated coverage throughout."--BOOK JACKET.
1. Introduction to operations management -- 2. Competitiveness, strategy, and productivity -- 3. Forecasting -- 4. Product and service design -- 5. Strategic capacity planning for products and services -- 6. Process selection and facility layout -- 7. Design of work systems -- 8. Location planning and analysis -- 9. Management of quality -- 10. Quality control -- 11. Inventory management -- 12. Aggregate planning -- 13. MRP and ERP -- 14. JIT and lean operations -- 15. Scheduling -- 16. Supply chain management -- 17. Project management -- 18. Waiting lines.
Includes index.
System requirements: Multimedia PC with Pentium 200 MHz or higher processor; 32-64 MB of RAM, up to 7 MB of hard disc space; Microsoft Windows 98, 2000, Professional, ME, or XP operating system; DVD-ROM drive, Microsoft Mouse, IntelliMouse, or compatible pointing device, Super VGA, 16-bit or higher monitor supporting 800x600 screen resolution, local bus video with 1MB or more of video memory, 16-bit sound card with speakers and headphones.
Keywords: Production management